2015
DOI: 10.1371/journal.pone.0131282
|View full text |Cite
|
Sign up to set email alerts
|

Different Ecological Niches for Ticks of Public Health Significance in Canada

Abstract: Tick-borne diseases are a growing public health concern as their incidence and range have increased in recent decades. Lyme disease is an emerging infectious disease in Canada due to northward expansion of the geographic range of Ixodes scapularis, the principal tick vector for the Lyme disease agent Borrelia burgdorferi, into central and eastern Canada. In this study the geographical distributions of Ixodid ticks, including I. scapularis, and environmental factors associated with their occurrence were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…The NARR has already been used as reference for other reanalysis projects including the California Reanalysis Downscaling at 10 km (CaRD10) ( Kanamaru and Kanamitsu 2007 ). Other studies also support the use of the NARR for the analysis of climate processes ( Fall et al 2010 ). Following CMIP-WGCM-WGSIP (2011) , we used the NARR surface air temperature to estimate the bias of each GCM’s surface air temperature data at each grid point.…”
Section: Methodsmentioning
confidence: 81%
“…The NARR has already been used as reference for other reanalysis projects including the California Reanalysis Downscaling at 10 km (CaRD10) ( Kanamaru and Kanamitsu 2007 ). Other studies also support the use of the NARR for the analysis of climate processes ( Fall et al 2010 ). Following CMIP-WGCM-WGSIP (2011) , we used the NARR surface air temperature to estimate the bias of each GCM’s surface air temperature data at each grid point.…”
Section: Methodsmentioning
confidence: 81%
“…Other studies using the same sites or sampling sites in the region found consistent positive associations between the presence and abundance of I. scapularis ticks on animal hosts (rodents and deer) and temperature, accounting for a range of alternative potential drivers for tick occurrence including habitat, rodent host abundance, rodent host species diversity, animal-level variables (e.g., age, sex, reproductive status), deer density, rainfall, and the possibility of spatial autocorrelation ( Bouchard et al 2013a ; Bouchard et al 2013b ). Further field surveillance data in eastern Canada supported the importance of temperature in determining the spatial pattern of establishment of I. scapularis at a multiprovince geographic scale in eastern Canada ( Gabriele-Rivet et al 2015 ).…”
Section: Detection Of Lyme Disease Emergence In Canada and Its Attribmentioning
confidence: 82%
“…Since the submissions for tick identification after 1990 were mostly limited to ticks removed from humans or their domestic animals, there is insufficient power to detect this species. Farther north and west, Hlp is still found parasitizing a wide range of avian and mammalian hosts [63,64].…”
Section: Discussionmentioning
confidence: 99%